2018
DOI: 10.1159/000487183
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Rearrangements Caused by Double Monosomy in Wheat-Barley Group-7 Substitution Lines

Abstract: Interspecific or introgressive hybridization is one of the driving forces in plant speciation, producing allopolyploids or diploids with rearranged genomes. The process of karyotype reshaping following homoploid interspecific hybridization has not been studied experimentally. Interspecific hybridization is widely used in plant breeding to increase genetic diversity and introgress new traits. Numerous introgression stocks were developed for hexaploid wheat Triticum aestivum L. (2n = 6x = 42, genome AABBDD). Dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…These results indicate that the short arm and partial long arm of wheat chromosome 5D close to the centromere were replaced by P. huashanica chromosome 5Ns. Many studies found that homoeologous chromosomes are remarkably conserved and any missing genetic content is usually complemented by corresponding homoeologous chromosomes [34][35][36][37]. In the H8911 × Trs-372 cross, because Trs-372 only carries A and B genomes, chromosome recombination mainly occurred between the D and Ns genomes, in particular, the reciprocal translocation between wheat 5D and P. huashanica 5Ns chromosomes that generated a new 5DL-5NsL·5NsS chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the short arm and partial long arm of wheat chromosome 5D close to the centromere were replaced by P. huashanica chromosome 5Ns. Many studies found that homoeologous chromosomes are remarkably conserved and any missing genetic content is usually complemented by corresponding homoeologous chromosomes [34][35][36][37]. In the H8911 × Trs-372 cross, because Trs-372 only carries A and B genomes, chromosome recombination mainly occurred between the D and Ns genomes, in particular, the reciprocal translocation between wheat 5D and P. huashanica 5Ns chromosomes that generated a new 5DL-5NsL·5NsS chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…At present, substitution lines are mainly derived from five methods including spontaneous substitution, monosomic substitution, telosomic substitution, nullisomic backcrossing, and tissue culture [27,28,29,30]. In theory, the homoeologous chromosomes of three wheat subgenomes can be replaced with alien chromosomes, forming three different types of alien substitution lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 5BS.7BS and 5BL.7BL translocations had no signi cant effects on PH, tillers, spikelets, and TGW (Yang et al 2021). A previous study indicated that wheat chromosomes are involved in rearrangements, such as chromosomal breakage and fusion, during the introduction of barley chromosome 7H into wheat to generate a double monosomic accession (Danilova et al 2018). The presence of alien chromosomes easily leads to additional chromosome structural changes, which may further diversify the host chromosomes.…”
Section: Effects Of Rye Chromosomes On Genetic Recombination and Chro...mentioning
confidence: 99%